2021
DOI: 10.1186/s12052-021-00158-8
|View full text |Cite|
|
Sign up to set email alerts
|

European first-year university students accept evolution but lack substantial knowledge about it: a standardized European cross-country assessment

Abstract: Background Investigations of evolution knowledge and acceptance and their relation are central to evolution education research. Ambiguous results in this field of study demonstrate a variety of measuring issues, for instance differently theorized constructs, or a lack of standardized methods, especially for cross-country comparisons. In particular, meaningful comparisons across European countries, with their varying cultural backgrounds and education systems, are rare, often include only few co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 110 publications
4
25
0
Order By: Relevance
“…However, even in those cases where it can be found in textbooks, it is often controversial in terms of the formation of misconceptions among pupils. The same findings about the inadequacy of teaching evolution or the existing problems in teaching evolution were reached by Kuschmierz et al (2021), who call for the naming of problematic or under-represented teaching of evolutionary phenomena in the subject of biology, across 26 European countries. Paradoxically, on a pan-European scale, students in apprenticeship programmes with biology performed better in knowledge about evolution (Kuschmierz et al, 2021), but this was not confirmed in the context of the Slovak Republic -students in combination with biology did not perform better than students in other apprenticeship programmes in terms of knowledge about evolution.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, even in those cases where it can be found in textbooks, it is often controversial in terms of the formation of misconceptions among pupils. The same findings about the inadequacy of teaching evolution or the existing problems in teaching evolution were reached by Kuschmierz et al (2021), who call for the naming of problematic or under-represented teaching of evolutionary phenomena in the subject of biology, across 26 European countries. Paradoxically, on a pan-European scale, students in apprenticeship programmes with biology performed better in knowledge about evolution (Kuschmierz et al, 2021), but this was not confirmed in the context of the Slovak Republic -students in combination with biology did not perform better than students in other apprenticeship programmes in terms of knowledge about evolution.…”
Section: Discussionmentioning
confidence: 67%
“…This could have an impact on students' further knowledge of the subject. Kuschmierz et al (2021) adds that the sheer number of lessons related to the topic of evolution says nothing about the quality and effectiveness of teaching, and is therefore not a decisive factor for improving students' knowledge of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many people are not aware that mutations are random and have a range of effects; that the potential for adaptability is not unbounded; nor that 'survival of the fittest' refers to how organisms compare to each other, rather than some absolute fitness metric. Indeed, misconceptions are frequent and widespread across different demographic groups, including young students, teachers and the general public [35][36][37].…”
Section: (A) Misconceptions About Evolutionmentioning
confidence: 99%
“…Acceptance of evolution is also influenced by the total number of years spent in education [38], understanding of nature of science [47], attitudes towards science [48], knowledge/understanding of evolution [49], and gross domestic product per capita [50]. Additionally, there is still a debate about the relationship between acceptance and actual understanding of evolution with conflicting evidence for strong positive correlation [51], weak positive relationship [36,37,48], or no correlation at all [52].…”
Section: (B) Conflicting Culture and Valuesmentioning
confidence: 99%
“…The authors [ 18 ] then developed an instrument to measure attitudes and understanding across Europe and beyond, called the “Evolution Education Questionnaire on Acceptance and Knowledge” (EEQ). The measurement instrument was translated into several European languages, in the various Romance, Germanic, and Slavic branches, and was recently applied to 9200 first-year university students in 26 European countries [ 19 ].…”
Section: Introductionmentioning
confidence: 99%